A Meta-Analysis of Quantitative Trait Loci Associated with Stay-Green in Sorghum - Aquib, Ahmed; Nafis, Shadma (Journal of Tropical Crop Science, 2022)
A strong association between stay-green and post-flowering drought tolerance in sorghum has been established previously. In this study, a meta-analysis was conducted to find relevant genetic intervals that regulate stay-green in sorghum and thereby affect drought resilience. Meta-QTL analysis was performed to combine 115 QTLs mapped in previous studies and locate regions where recurrent QTLs occurred across experiments. This approach overcomes the constraints of a single QTL association experiment by increasing heterogeneity in populations and environments. The analysis included the construction of consensus maps, QTL projection, and QTL clustering. We report 32 Meta-QTL for stay-green and their position relative to genetic markers on the sorghum genome. The results from this study will facilitate future attempts aiming to improve and understand drought tolerance in Sorghum by the use of fine mapping and marker-assisted selection.